Penciptaan Tari Anak-anak Disabilitas Kami Tak Berbeda - Kuncoro, Jonet Sri; supendi, eko (Acintya, 2020)
ABSTRACT  The dance work entitled "Kami Tak Berbeda” (We Are Not Different) is a dance work specifically for children with disabilities. This work is a development of previous works made by Jonet Sri Kuncoro. In this work combines deaf children, the blind, and physically disabled. This work is supported by three extraordinary schools in Solo Raya, namely SLB Cangakan Karanganyar and SLB B-C Hamong Putro Sukoharjo. This work was created with the approach of developing a pattern of six arising dots cell consisting of three rows with two dots on Braille letters made of 4/4 measure and sign language for the deaf and poetry reading. The peak process of the practice is a dance performance that has a form of performance combining the development of Braille letters pattern with sign language in group choreography supported by musical accompaniment as a power to express the atmosphere. Keywords: Disability, Deaf, Blind, Braille, Sign Language.  ABSTRAK Karya tari berjudul “Kami Tak Berbeda” merupakan karya tarian yang dikhususkan untuk anak-anak disabilitas. Karya ini merupakan pengembangan dari karya-karya sebelumnya yang dibuat oleh Jonet Sri Kuncoro. Pada karya ini menggabungkan antara anak-anak tuna rungu, tuna netra, dan tuna daksa. Karya ini di dukung oleh tiga sekolah luar biasa Kota Solo Raya, yaitu SLB Negeri Cangakan Karanganyar, dan SLB B-C Hamong Putro Sukoharjo. Karya ini diciptakan dengan pendekatan pengembangan pola enam sel titik timbul yang terdiri dari tiga baris dengan dua titik pada huruf Braille yang dibuat birama 4/4 dan bahasa isyarat bagi tuna rungu serta pembacaan puisi. Sebagai proses puncak dari latihan adalah pergelaran karya tari yang memiliki bentuk pertunjukan memadukan pengembangan pola huruf Braille dengan bahasa isyarat dalam koreografi kelompok yang didukung oleh iringan musik sebagai daya ungkap suasana. Kata kunci: Disabilitas, Tuna Rungu, Tuna Netra, Braille, Bahasa Isyarat.